THE USE OF AMPPD AS AN ALTERNATIVE SUBSTRATE FOR AP-MEDIATED DETECTION OF NONRADIOLABELED DNA PROBES IN EUCALYPTUS-SALIGNA - Pardini, MID; Wolff, JLC; Lopes, C. R. (Soc Brasil Genetica, 1993)
We present a non-radioactive alternative to Southern's (J. Mol. Biol. 98: 503-517, 1975) DNA-DNA hybridization technique. The use of AMPPD - Disodium 3-(4-Methoxyspiro {1,2-dioxetane-3,2'tricyclo[3.3.1.1(3,7)]decan}-4-yl)phyenyl phosphate as an alternative substrate for AP-mediated detection of digoxigenin-11 dUTP-labeled probes made possible the simple and nonhazardous reuse of blots. We used 0.8 % agarose gels containing 30 mug per lane of Eucalyptus saligna DNA, digested with Eco RI, electrophoresed and blotted on to nylon membranes (Hybond-N, Amersham, UK), using the Southern blotting procedure, and UV irradiated for one minute for DNA fixation. The hybridizations were carried out overnight with digoxigenin labeled random inserts of E. saligna DNA by using the Genius Kit (Boehringer Mannheim). Detection of the DNA-DNA hybrids was performed in the presence of 0.5% blocking agent and the substrates NBT/BCIP were replaced by 0.26 mM AMPPD in the final alkaline assay buffer (50 mul/cm2). After membrane incubation for five minutes at room temperature in a sealed plastic bag, the AMPPD solution was retrieved and stored at 4-degrees-C for reuse. A Kodak X-BRAF QA-S film was pressed firmly onto the bag containing the wet membrane, exposed for two to six hours and then developed. After use, the probes were stripped off and the blots reutilized, three times so far, with the same results.